Evaluation of Sorghum Emergence and Grain Yield Response to Seeding Density and Plant Spacing Attained Using the OSU Hand Planter - Nambi, Eva; Aula, Lawrence; Oyebiyi, Fikayo B.; Eickhoff, Elizabeth M.; Omara, Peter; Carpenter, Jonathan; Raun, William R. (Communications in Soil Science and Plant Analysis, 2021)
Plant spacing and density are important metrics in crop production because they impact the plant’s ability to utilize resources and attain full yield potential. Planting sorghum (Sorghum bicolor (L.) Moench) in a more narrow spacing brings about phytochrome-mediated responses, where plants develop narrow leaves, long stems, fewer roots, and this is linked to competition that plants develop for nutrients like nitrogen (N). The Oklahoma State University hand planter (OSU-HP) can improve plant homogeneity and midseason placement of N. However, this crop production tool alongside other agronomic practices have not been adequately evaluated for improving sorghum grain yields. The objective of this work was to evaluate the response of sorghum to planting methods, the number of seeds per hole, within row spacing, and N rate. A randomized complete block design with 13 treatments replicated 3 times was used in this study. The treatments included different combinations of 3 planting methods (John Deere [JD], OSU-HP, and stick planter [check]), 3 within-row spacings (10, 30, and 60 cm), 3 different number of seeds per hole (1, 3, and 6) and 3 N rates (0, 30 and 60 kg ha−1). Average grain yield with 3 seeds per hole was at least 18% higher than the yield range of 0.7 to 4.6 Mg ha−1 achieved with 1 or 6 seeds per hole. This study demonstrated that the production of sorghum using sound agronomic practices could improve yield.
Keywords: Sorghum; Nitrogen; Urea incorporation; Hand planter; Plant spacing